Voicing Teachers’ Perspectives on Professional Development in Literacy Education Through Narrative Inquiry - Syed, Kahlida Tanvir (Alberta Journal of Educational Research, 2008)
This article explores two beginning Canadian teachers’ experiences of professional development in literacy education. Differences and parallel tensions between the Canadian teachers’ and my own experiences as a teacher and teacher educator in Pakistan were identified through narrative inquiry. The significance of this article is found in the expression of seven necessary conditions for successful professional development: appreciation and awareness of teachers’ internal quest for learning; teachers’ involvement in their own professional development; promotion of active, critical reflection; sharing multiple perspectives in collective conversation; providing time for internal reflection; a democratic context for professional development; and supporting teachers’ efforts to develop their professional knowledge base.